Mindfulness Mediates the Effect of a Psychological Online Intervention for Psychosis on Self-Reported Hallucinations: A Secondary Analysis of Voice Hearers From the EviBaS Trial - Lüdtke, Thies; Platow-Kohlschein, Heike; Rüegg, Nina; Berger, Thomas; Moritz, Steffen; Westermann, Stefan (Frontiers in Psychiatry, 2020)
Background: Psychological online interventions (POIs) could represent a promising approach to narrow the treatment gap in psychosis but it remains unclear whether improving mindfulness functions as a mechanism of change in POIs. For the present study, we examined if mindfulness mediates the effect of a comprehensive POI on distressing (auditory) hallucinations. Methods: We conducted a secondary analysis on voice hearers (n = 55) from a randomized controlled trial evaluating a POI for psychosis (EviBaS; trial registration NCT02974400, clinicaltrials.gov). The POI includes a module on mindfulness and we only considered POI participants in our analyses who completed the mindfulness module (n = 16). Results: Participants who completed the mindfulness module reported higher mindfulness (p = .015) and lower hallucinations (p = .001) at post-assessment, compared to controls, but there was no effect on distress by voices (p = .598). Mindfulness mediated the POI’s effect on hallucinations (b = -1.618, LLCI = -3.747, ULCI = -0.054) but not on distress by voices (b = -0.057, LLCI = -0.640, ULCI = 0.915). Limitations & discussion: Completion of the mindfulness module was not randomized. Hence, we cannot draw causal inferences. Even if we assumed causality, it remains unclear which contents of the POI could have resulted in increased mindfulness and reduced hallucinations, as participants completed other modules as well. In addition, confounding variables could explain the mediation and the sample size was small. Nonetheless, the overall pattern of results indicates that a POI is likely to improve mindfulness, and that increased mindfulness could partially explain the POI’s efficacy.